Women Soldiers in the Year of the October Revolution: Images in Fiction Женщины-солдаты в год Октябрьской революции: образы в художественной литературе - Simonova, Olga (Informa UK Limited, 2025)
The article examines the unique phenomenon of all-female battalions in revolutionary Russia in 1917 and the images of female volunteers in them within the framework of literary studies. The fictional texts are analyzed using the methodological development of types of female soldiers. The difficulty in creating a positive character for the writers lay in the fact that it was an atypical example that challenged the gender order of the time. In the text “From the Diary of Soldier Kirova” (1917), Leonid Grigorov creates a new
military femininity supplemented by ‘masculine’ features. In the fiction of 1920s, the images of the defenders of the Winter Palace were generalized as physically weak, frivolous and lecherous characters. Veniamin Kaverin, in his novel Nine Tenths of a Fate (1925), overcomes this predetermination by showing the exclusivity of his heroine: her cross-dressing testifies to the ‘correct’ fulfilment of her role as a warrior. In the end, however, her destiny is reduced to ‘women’s happiness,’ thus nullifying the achievements of the war
and the revolutionary era in changing the gender order.